Aggregate impacts of a gift of time - Jungmin Lee; Daiji Kawaguchi; Daniel S. Hamermesh (Institute for the Study of Labor (IZA), 2011)
How would people spend additional time if confronted by permanent declines in market work? We examine the impacts of cuts in legislated standard hours that raised employers' overtime costs in Japan around 1990 and Korea in the early 2000s. Using time-diaries from before and after these shocks, we show that these shocks were effective - per-capita hours of market work declined discretely. The economy-wide drops in market work were reallocated solely to leisure and personal maintenance. In the absence of changing household technology a permanent time gift leads to no increase in time spent in household production by the average individual.
urn:nbn:de:101:1-201201107486
Keywords: J22; J11; E24; 330; time use; household production; demand shock; macroeconomic effects; Arbeitszeit; Dauer; Zeitverwendung; Freizeit; Hausarbeit; Haushaltsproduktion; Japan; Südkorea